PENGUATAN DAN PENGEMBANGAN JASA SERVIS MESIN JAHIT PAK HARTO DI SUKOHARJO - Ridwan Afandi; Sutiyoko; Suparni; Nur Wahid Supriyadi (CV. Multi Kreasi Media, 2023)
Sewing machine workshop / service is one of the businesses that has developed a lot in society along with the development of science and technology. Pak Harto's sewing machine service has been established since around 1993 and runs its business in accordance with existing conditions. The number of employees as many as 4 people including the owner and financial bookkeeping has not been carried out neatly and computer-based. This certainly reduces the speed of decision-making of the service. The warehousing stock has also not been neatly arranged so that it prolongs the disbursement of spare parts to be installed. The implementation of the activity program has been carried out in part by providing assistance in bookkeeping and marketing management. Bookkeeping management is carried out by making a stock book of goods available at the beginning of each month and a daily sales book for each month. Marketing improvement is carried out by creating accounts and stalls in one of the marketplaces. The results of the program implementation are still in the implementation and monitoring stage. Activities under the terms of the program will end in 2022, but the implementation of the program is expected to continue to be carried out independently by partners. Monitoring the implementation of the program is continuously carried out taking into account the capabilities of human resources.